Assessment of the general population knowledge about the emergence of Nipah virus outbreak in Bangladesh: A nationwide cross-sectional study - Mobin Ibne Mokbul; Shuvajit Saha; Samiha Nahar Tuli; Fatema Binte Nur; A.M. Khairul Islam; Tariful Islam; Shirsho Shreyan; Alok Bijoy Bhadra; Golam Dastageer Prince; Irfath Sharmin Eva; Mustari Nailah Tabassum; Ferdous Wahid; et al. (Journal of Virus Eradication)
The emergence of the Nipah virus (NiV) poses a significant global health threat, particularly in South-East Asian countries. This cross-sectional nationwide study is a pioneer in assessing knowledge levels of NiV outbreak among the general population in Bangladesh. It was conducted among the general population of Bangladesh from 15th January to 10th February 2024. A conveniently selected sample of individuals participated in the assessment of their knowledge about NiV. A semi-structured questionnaire was used as the data collection tool. After data curation, a total of 2121 responses that met the inclusion criteria were retained for analysis. Among 2121 participants, 69.38 % were aware of NiV. Overall, 62 % demonstrated good knowledge of the virus. The main sources of information were social media (29.9 %), television (25.41 %), educational institutions (18.95 %), newspapers (13.65 %), friends (6.39 %), and workplaces (5.91 %). Multivariate logistic regression analysis showed that participants aged 31–40 years had lower odds of poor knowledge (OR = 0.57, 95 % CI: 0.39–0.82, p < 0.01) compared to those aged 21–30. Females had higher odds of poor knowledge (OR = 1.38, 95 % CI: 1.05–1.81, p = 0.02) than males. Lower education levels were associated with higher odds of poor knowledge. Moreover, non-healthcare workers also had higher odds of poor knowledge compared to healthcare workers. There were regional differences, with varying odds in Rangpur (OR = 0.43, 95 % CI: 0.26–0.70, p < 0.01), Khulna (OR = 1.70, 95 % CI: 1.10–2.61, p = 0.01), and Mymensingh (OR = 2.77, 95 % CI: 1.70–4.53, p < 0.01) compared to Dhaka. The current study underscores the importance of evidence-based educational strategies, and may guide government and policymakers to design future targeted interventions to enhance public health literacy and mitigate the spread of NiV in Bangladesh as well as in its neighbouring countries.